Implementation of a Modular MIoT Platform for Real-Time Vital Sign Monitoring - Arnesen, Jonas; Elvevold, August; Ghose, Debasish; Lin, Yuan (Proceedings (IEEE International Conference on Healthcare Informatics. Online), 2025)
This work introduces a modular and interoperable Medical Internet of Things (MIoT) system for real-time vital sign monitoring, including heart rate, respiration rate, oxygen saturation, temperature, and blood pressure. The system integrates multiple wearable MIoT devices with a secure mobile gateway, while a backend microservice handles authentication, stores time-series data in TimescaleDB, and supports an interactive dashboard for visualization and decision support. Experiments with test subjects validated system performance and feasibility, while usability tests demonstrated its potential for real-world deployment.